Toxicity Analysis of Hybrid Nanodiamond/Fe3O4 Nanoparticles on Allium cepa L - Bhaludra Chandra Sekhar Singh (Journal of Toxicology)
Background and Objective. The study of the toxicity of hybrid nanoparticles is necessary before they are synthesized in the laboratory and used in any particular applications. The toxic behaviour of nanoparticles can cause harm for the living species on the Earth. The production of biocompatible hybrid nanoparticles is important. Hence, this study is aimed at determining that nanodiamond/Fe3O4 hybrid nanoparticles were prepared and used for the toxicity analysis on Allium cepa L. Materials and Methods. The chemicals of hydrochloric acid, nitric acid, FeCl3.6H2O, FeCl2.4H2O, NaCl, and NaOH (Sigma-Aldrich chemicals, USA) were utilized in this study. A statistical analysis was performed on the results with a prevalence of p<0.05. Results. A novel ND/Fe3O4 nanocomposite material was successfully synthesized by the in-situ method and characterized by various characterization techniques. The analysis of X-ray diffraction indicated the formation of an ND/Fe3O4 nanocomposite with both participating phases. The saturation magnification of the ND/Fe3O4 nanocomposite is 13.2 emu/g, whereas for a pure Fe3O4 nanomaterial, it is 47 emu/g. The weight rates of ND and Fe3O4 existent in the nanocomposite are 28% and 72%, respectively. From the electrical conductivity analysis, ND/Fe3O4 exhibits conductivity in the order of 27 times more compared to ND. Conclusion. The result implies that the product ND/Fe3O4 has both magnetic and electrical properties. The biocompatibility of the synthesized ND/Fe3O4 material was studied based on the in-vitro method.